Integrating Equity and Efficiency in Applied Welfare Economics - Boadway, Robin (Quarterly Journal of Economics, 1976)
I. Introduction, 541.—II. A general cost-benefit rule for equity and efficiency, 542.—III. Some special cases, 547.—IV. Conclusions, 555.